Feeding Disorders in Children With Autism Spectrum Disorders Are Associated With Eosinophilic Esophagitis. Issue 4 (October 2016) - Heifert, Theresa A.; Susi, Apryl; Hisle-Gorman, Elizabeth; Erdie-Lalena, Christine R.; Gorman, Gregory; Min, Steve B.; Nylund, Cade M.
ABSTRACT: Objectives: Eosinophilic esophagitis (EoE) can present as food selectivity or feeding disorders in children. Children with autism spectrum disorders (ASDs) commonly demonstrate behavioral food selectivity in type and texture, which often leads to the diagnosis of feeding disorder. We sought to evaluate the association of ASD with EoE. Methods: A retrospective matched case-cohort study was performed using the Military Health System database from October 2008 to September 2013. We performed a 1:5 case-control match by age, sex, and enrollment timeframe. Feeding disorders, EoE, and atopic disorders were defined using diagnostic and procedure codes. Results: There were 45, 286 children with ASD and 226, 430 matched controls. EoE was more common in children with ASD (0.4%) compared with controls (0.1%). Feeding disorders were associated with EoE in both children with ASD and controls. Feeding disorders also had a higher odds ratio for EoE compared with other atopic conditions, among both children with ASD (7.17, 95% confidence interval [CI] 4.87–10.5) and controls (11.5, 95% CI 7.57–17.5). Compared with controls with a feeding disorder, children with ASD and a feeding disorder had no difference in the rate of diagnosed EoE (0.85, 0.95% CI 0.39–1.88). Conclusions: Children with ASD are more likely to be diagnosed with EoE compared with controls; however, among children with feeding disorders, there is no difference in the odds of EoE. A diagnosis of feeding disorder was strongly associated with EoE. Feeding disorders in children with ASD should not be assumed to be solely behavioral and an esophagogastroduodenoscopy should be performed to evaluate for EoE. Abstract : Supplemental Digital Content is available in the text